Reading - Greenall, Simon (Cambridge Skills for Fluency, 1993)
Develops reading skills by introducing learners to a wide variety the authentic texts. The texts have been selected to be of real interest to the learner and they are supported by carefully graded tasks and activities designed to increase the pre-intermediate learner´s involvement and confidence in reading in english